Characteristic analysis and assessment of disharmony oscillation in multi-VSCU system - Qiyi Yu; Yi Tang (International Journal of Electrical Power & Energy Systems)
Previous studies have shown that disharmony among two or three voltage-source-controlled units (VSCUs) may occur on alternating current (AC) transmission lines under steady-state or quasi-static operating condition. As the number of VSCUs increases in a local AC power grid, the probability of multi-VSCU disharmony occurrence increases which may lead to more complex oscillation. For disharmony in multi-VSCU system, this paper analyzes the disharmony oscillation (DHO) characteristics on power grid side and evaluates the degree of disharmony. First, this paper classifies the frequency disharmony problem and elaborates on the equivalent model of the local AC power grid with multiple disharmonized VSCUs. Second, load and line flow oscillation characteristics under disharmony operating condition are discussed. The index for evaluating the degree of disharmony is defined. Finally, case studies based on different load levels and topologies show the abnormal characteristics of power flow and variation law between the degree of disharmony and power flow. The relevant results can provide a reference for monitoring disharmony and verifying DHO suppression methods.